2019
DOI: 10.1002/vnl.21726
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Fly Ash‐Based Mesoporous Aluminosilicate Oxides Loaded with Zinc and its Synergistic Fire Resistancy in Polypropylene

Abstract: A kind of mesoporous aluminosilicate oxides (MAOs) were fabricated from industrial waste, coal fly ash. After loaded with zinc on MAO, the product MAO-Zn was characterized by Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and scanning electron microscopy (SEM). MAO-Zn was incorporated with intumescent flame retardant (IFR) together and used in polypropylene (PP). Basic characterization including limiting oxygen index (LOI), vertical burning test (UL-94), and cone calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…CFA from an Indian coal gasification plant underwent NaOH fusion followed by hydrothermal treatment in order to produce basic CFA-derived zeolite X (NaX/CFA) [23] and, after acidification, HX/CFA. Many studies are found in literature on different applications of CFA-derived zeolites, such as adsorbent material for gas and water treatment [23,24] or binder for flame retardants [25]. As far as we know, just a few of these studies regard experimentations as catalysts in pyrolysis of plastics [26,27] and none have investigated the effects of CFA-derived zeolites on a real plastic waste.…”
Section: Introductionmentioning
confidence: 99%
“…CFA from an Indian coal gasification plant underwent NaOH fusion followed by hydrothermal treatment in order to produce basic CFA-derived zeolite X (NaX/CFA) [23] and, after acidification, HX/CFA. Many studies are found in literature on different applications of CFA-derived zeolites, such as adsorbent material for gas and water treatment [23,24] or binder for flame retardants [25]. As far as we know, just a few of these studies regard experimentations as catalysts in pyrolysis of plastics [26,27] and none have investigated the effects of CFA-derived zeolites on a real plastic waste.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, addition of FA showed a little enhancement in thermal stability of the IFR/PP, in which T 5% increased by 7°C, and the residue at 800°C upgraded from 8.7% to 11.4%. This could be attributed to the presence of SiO 2 and Al 2 O 3 in the FA that accelerated charring and made the char layer more compact and tougher 31,32 …”
Section: Resultsmentioning
confidence: 99%
“…And the effective diameter of the microporous for 3A, 4A and 5A is approximately 3, 4 and 5 Å, respectively . Interestingly, some studies found MA became more active after loaded by rare earth metal . Such as La 3+ , it will be inserted the channels and chelated by Si‐O groups of the MA.…”
Section: Introductionmentioning
confidence: 99%